Efficient multiplication of a Semliki Forest virus chimera containing Sindbis virus spikes. - Smyth, J (1997)
Using the Semliki Forest virus (SFV) and Sindbis virus (SIN) cDNAs we have constructed recombinants in which the spike genes were exchanged. Analyses of expression showed that the SFV/SIN(spike) RNA directed efficient assembly of infectious virus, whereas the reciprocal SIN/SFV(spike) RNA was completely unable to assemble virus. This was apparently due to a defective capsid-spike interaction.